A PLATINUM-LINKED CYCLIC PORPHYRIN TRIMER - Mackay, L; Anderson, H; Sanders, J (1992)
A cyclic trimeric porphyrin host is synthesised from monomer via alkyne-platinum-alkyne linkages; binding of the octahedral aluminum tris[3-(4-pyridyl)acetylacetonate] guest ligand into the complementary cavity of the host induces an asymmetry, which is readily detected by NMR spectroscopy.